Baranugun kang Tarangban a Shounen Manga. - Bagarinao, Andrea
Manga is a very popular form of popular literature. It is the Japanese term for comics, but outside Japan, ?manga? is exclusively used to refer to Japanese comics or Japanese style comics. Shounen manga are comics intended for male readers. They focus on action, adventures, and development of male heroes. The Rescue, the latter part of the third courting adventure consisted in The Epic of Labaw Donggon, was enhanced using styles and concepts of shounen manga. The themes and characters, which are very important elements of manga, involved in the epic and the story itself were explored and improved to create the shounen manga, Baranugun kang Tarangban.